Phenotypic responses of coral reef fishes to extreme and novel environments - D'Agostino, Daniele (2020)
In an increasingly variable and rapidly warming global environment, there is still little consensus as to the biological mechanisms that may facilitate population persistence of coral reef fishes. While a range of studies have shown substantial losses of coral reef fishes with environmental impacts, there are an increasing number of studies which have shown the importance of plasticity in behavioural, demographic and life-history traits in sustaining coral reef fish populations. As such, the main goal of this thesis was to investigate whether phenotypic plasticity plays an important role in determining coral reef species survival in an increasingly challenging environment. To do so, I focused on three phylogenetically and ecologically diverse coral reef fish species that thrive in the extreme environment of the Arabian/Persian Gulf (hereafter ‘Arabian Gulf’). Within the Arabian Gulf summer temperatures are in line with those projected for the tropical oceans by 2100, while winter condition can be so severe as to induce cold water coral bleaching. Moreover, the Arabian Gulf’s waters are characterized by hypersaline conditions that are the highest reported for coral reefs. These conditions provide an ideal setting to investigate the traits which allow resident coral reef fish populations to cope with predicted extremes and high variability in environmental conditions. In parallel, as many Red Sea coral reef fishes have recently invaded and established populations in the Mediterranean Sea (i.e. Lessepsian migration), I focused on the potential role of phenotypic plasticity in facilitating marine fish invasion within a temperate rocky reef ecosystem, as well as investigating the ecological interaction between invasive species and the wider native and non-native fish community.